PENDIDIKAN BERBASIS NEUROSCIENCE: INOVASI METODE PEMBELAJARAN UNTUK MENINGKATKAN KUALITAS PEMAHAMAN PESERTA DIDIK - Amrullah, Nikmah; Syamsul Aripin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Innovation in education has become a primary necessity in the current era of globalization and technology. One emerging innovative approach is neuroscience-based education, which integrates the understanding of brain mechanisms into the learning process. This study aims to examine the application of neuroscience principles, such as neuroplasticity and emotional engagement, in enhancing students' comprehension quality. The method used is a literature review with a descriptive qualitative approach. Data were collected from various relevant academic sources and analyzed using content analysis techniques. The findings reveal that learning strategies emphasizing neuroplasticity principles and involving students' emotional aspects can improve information retention, learning motivation, and critical thinking skills. This approach also fosters the creation of a more supportive and adaptive learning environment tailored to students' needs. Therefore, neuroscience-based education can serve as a strategic innovation in developing effective and student-centered learning in the 21st century. Continuous training for educators and further empirical research are recommended to enrich the implementation of this approach across various educational contexts.